How the digital revolution is reshaping water management and policy: A focus on Spain - Expósito-García, Alfonso; Díez Cebollero, Esther (ELSEVIER, 2025)
The water sector is experiencing a transformative shift through digitalisation, integrating advanced technologies like IoT devices, AI, and digital twins into water management and policy practices. These advanced technologies address critical challenges such as water scarcity and hydro-climatic extreme events by improving monitoring, management, and decision-making transparency. This paper examines the impacts of digitalisation on water management and policy by analysing the Spanish case study. Findings reveal practical benefits and identify significant challenges to its adoption in the water cycle at different managerial scales. To address these challenges, we propose recommendations emphasising equitable access, capacity-building, and supportive regulatory frameworks.
Keywords: Economía ambiental; Recursos hidráulicos; Sistemas de control inteligente; Cambios climáticos; Ciclo hidrológico; Digitalisation; Smart water systems; Sustainability; Resilience; Inteligencia artificial